Registration of 'ARS Crescent' soft white winter club wheat. Issue 3 (6th August 2021) - Garland Campbell, Kim; Allan, Robert; Burke, Adrienne; Chen, Xianming; DeMacon, Patricia; Higginbotham, Ryan; Engle, Doug; Johnson, Stephen; Klarquist, Emily; Mundt, Chris; Murray, Timothy; Morris, Craig; et al.
Abstract: Soft white club winter wheat ( Triticum aestivum L. ssp. compactum ) represents 8–10% of the wheat crop in Washington, but most of the current club wheat production is located in the <350‐mm annual precipitation zone. Our goal was to develop a club wheat cultivar targeted to the >350‐mm annual precipitation zones of the Pacific Northwest. 'ARS Crescent' (Reg. no. CV‐1181, PI 665048), an awned white‐kernel club wheat, was selected using the bulk‐pedigree breeding method from the cross 'Dusty'//'Madsen' sib/Dusty///WA7665/'Rulo'. At the time of release, ARS Crescent was rated as resistant to stripe rust races PSTv‐4 and PSTv‐51, segregating for resistance to race PSTv‐37, and susceptible to races PSTv‐14 and PSTv‐40 in the seedling stage. In the adult‐plant stage in the field, ARS Crescent has demonstrated high‐temperature adult plant resistance to stripe rust. Several years after release, the grain yields of ARS Crescent are equivalent to the club wheat 'Bruehl' and to soft white wheat checks for all growing regions. ARS Crescent combines better test weight than Bruehl with better resistance to environmental conditions that result in low falling numbers in wheat. ARS Crescent has excellent milling properties and greater sponge cake volume than other club wheat cultivars and increases the quality of the crop in Washington. Core Ideas: ARS Crescent has excellent end use quality. Grain yields of ARS Crescent are competitive with soft white winter wheat cultivars. ARS Crescent has good resistance to low falling numbers. ARS Crescent has adult plant resistance to stripe rust. ARS Crescent increases the quality of exports of soft wheat.